Influence of gamma radiation on the antioxidant properties of edible chestnuts - Antonio, Amilcar L. (2010)
As seasonal products chestnut have to be postharvest treated to increase the shelf-life. Several problems are associated with traditional preservation methods. These are a decreasing in quality due to dehydration and contamination with insects and microbes including secondary metabolites, e.g.: mycotoxin. The most common preservation method for chestnuts is the use of chemical fumigation with methyl bromide. Methyl bromide is a toxic agent and has been banned according to the Montreal Protocol due to its adverse effects on human health and the environment. Following the recommendations of a scientific committee of the United Nations Environmental Program (UNEP), Methyl Bromide Technical Options Committee (MBTOC), food irradiation is a possible feasible option. This pre1iminary study evaluated the influence of gamma irradiation in the antioxidant potential of chestnut fruits and skins. Results showed that irradiation of chestnuts at low irradiation doses, 0.27 kGy and 0.54 kGy, could affected the skin and fruit properties differently.